The Psychological Challenge of Late-Life Vision Impairment: Concepts, Findings, and Practical Implications - Hans-Werner Wahl (Journal of Ophthalmology)
The intention is to summarize the body of evidence speaking to the psychological challenges faced by visually impaired older adults, as well as their coping efforts. This evidence is substantiated by a rich set of concepts, theories, and empirical findings that have accumulated under the umbrella of age-related psychoophthalmology (APO). I introduce the field of APO and continue with a discussion of important concepts and theories for a better understanding of adaptational processes in visually impaired older adults. I then summarize the most relevant and most recent data from four areas: (1) everyday competence, (2) cognitive functioning, (3) social functioning, and (4) subjective well-being-related outcomes, depression, and adaptational processes. Thereafter, major insights related to the current state-of-the art psychosocial interventions with visuallyimpaired older adults are reviewed. I close with the need that the public health community should become more aware of and address the psychosocial needs of visually impaired older adults.